Nursing Students’ Knowledge, Attitudes, and Self-Efficacy in Transcultural Palliative End-of-Life Care: A Multicenter Structural Equation Modelling Study - Ni Luh Putu Inca Buntari Agustini (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2025)
Background: Palliative End-of-Life Care (PEOLC) is a core competency for nursing students, requiring the ability to deliver holistic and culturally sensitive care to patients and families in the final stage of life. A transcultural nursing approach is recognized for fostering cultural sensitivity, knowledge, positive attitudes, and self-efficacy. However, evidence on how these factors interact remains limited in Indonesian nursing education. This study examined the relationships among knowledge, attitudes, and self-efficacy related to transcultural nursing-based PEOLC among nursing students using Structural Equation Modelling.Methods: A quantitative analytic, cross-sectional design was applied in a multicenter setting across several Indonesian nursing higher-education institutions. Participants were active nursing students recruited through convenience sampling who provided informed consent. Data were collected using standardized, validated questionnaires (item validity, r ≥ 0.30; Cronbach’s α ≥ 0.80), which measured knowledge, attitudes, and self-efficacy. Partial Least Squares–Structural Equation Modelling assessed direct and indirect relationships among variables.Results: A total of 330 students participated. SEM analysis revealed that knowledge had a significant influence on attitudes (β = 0.528, p < 0.05) and self-efficacy (β = 0.146, p < 0.05). Attitudes also significantly mediated the effect of knowledge on self-efficacy (β = 0.6, p < 0.05). The final model indicated goodness of fit (χ² = 2029.657; SRMR = 0.031; NFI = 0.905).Conclusion: Knowledge, attitudes, and self-efficacy regarding transcultural nursing–based PEOLC are strongly interrelated among Indonesian nursing students. These findings underscore the importance of integrating transcultural approaches and experiential learning into nursing curricula to enhance students’ confidence and readiness to deliver culturally responsive end-of-life care.